Switched LPV Glucose Control in Type 1 Diabetes - Colmegna, Patricio Hernán (2016)
Objective: The purpose of this paper is to regulate the blood glucose level in Type 1 Diabetes Mellitus patients with a practical and flexible procedure that can switch among a finite number of distinct controllers, depending on the user's choice. Methods: A switched linear parameter-varying controller with multiple switching regions, related to hypo-, hyper-, and euglycemia situations, is designed. The key feature is to arrange the controller into a framework that provides stability and performance guaranty. Results: The closed-loop performance is tested on the complete in silico adult cohort of the UVA/Padova metabolic simulator, which has been accepted by the U.S. Food and Drug Administration in lieu of animal trials. The outcome produces comparable or improved results with respect to previous works. Conclusion: The strategy is practical because it is based on a model tuned only with a priori patient information in order to cover the interpatient uncertainty. Results confirm that this control structure yields tangible improvements in minimizing risks of hyper-and hypoglycemia in scenarios with unannounced meals. Significance: This flexible procedure opens the possibility of taking into account, at the design stage, unannounced meals and/or patients' physical exercise.